The Effect of Airline Ticket Selling Prices and Advertising Attractiveness on Buying Interests of Airline Service Users on Super Air Jet Airlines at Hang Nadim International Airport Batam - Mohammad Sisabilillah Siregar; You She Melly Anne Dharasta (CV. Rayyan Dwi Bharata, 2023)
Fast and efficient transportation is a must, with transportation we are able to meet the needs of life. With so many enthusiasts in the aviation industry, airline entrepreneurs must meet these needs. This study aims to determine whether there is an Effect of Flight Ticket Selling Prices and Advertising Attractiveness on the Buying Interest of Flight Service Users on Super Air Jet Airlines at Hang Nadim International Airport Batam. This research method uses a quantitative approach. The number of samples in this study was 100 respondents. The respondents in this study are people or users of Super Air Jet air transportation services. Sampling using random sampling technique. Data collection techniques by giving questionnaires to respondents. In analyzing this, validity and reliability tests are used, multiple linear regression tests, f tests (simultaneous) and t tests (partial) and Coefficient of determination (R2). The test results show that: Partially affects the interest in buying tickets for super air jet air transport users at Hang Nadim International Airport Batam. The test results partially show that the price (X1) has a significant value of the price variable of 0.000 ≤ 0.05 so that it can be concluded that H1 is accepted or the price variable (X1) affects buying interest (Y) and Ho is rejected. Ad attractiveness (X2) has a significant value of ad attractiveness variable of 0.000 ≤ 0.05 so it can be concluded that H1 is accepted or ad attractiveness variable (X2) affects buying interest (Y) and Ho is rejected. Simultaneously affects the interest in buying tickets for super air jet air transport users at Hang Nadim International Airport Batam. The test results are obtained from the F test results with significant values of 0.000 ≤ 0.05. So it is concluded that H1 is accepted or in other words price (X1) and advertising attractiveness (X2) simultaneously affect buying interest (Y) and Ho is rejected